2021
DOI: 10.20900/agmr20210008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Brain through Aging Eyes

Abstract: The eye and brain share common mechanisms of aging and disease, thus the retina is an essential source of accessible information about neurodegenerative processes occurring in the brain. Advances in retinal imaging have led to the discovery of many potential biomarkers of Alzheimer’s disease, although further research is needed to validate these associations. Understanding the mechanisms of retinal disease in the context of aging will extend our knowledge of AD and may enable advancements in diagnosis, monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Communication between the brain and the retina occurs through retinal ganglion cells, connecting with the cortex through the optic nerve. Like the blood–brain barrier, the blood-retinal barrier plays a role in regulating the supply of oxygen and glucose and protecting the retinal microenvironment against exposure to molecules, in this case, especially to inflammatory cytokines commonly circulating in patients with DM and its comorbidities [ 82 , 83 ]. The production or activation of inflammatory cytokines at the brain level can lead to insulin action resistance in the brain, resulting in deterioration of brain processes such as neuron survival, dendritic plasticity, synaptic function, learning, and memory [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication between the brain and the retina occurs through retinal ganglion cells, connecting with the cortex through the optic nerve. Like the blood–brain barrier, the blood-retinal barrier plays a role in regulating the supply of oxygen and glucose and protecting the retinal microenvironment against exposure to molecules, in this case, especially to inflammatory cytokines commonly circulating in patients with DM and its comorbidities [ 82 , 83 ]. The production or activation of inflammatory cytokines at the brain level can lead to insulin action resistance in the brain, resulting in deterioration of brain processes such as neuron survival, dendritic plasticity, synaptic function, learning, and memory [ 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have observed an association between corneal neurodegeneration findings with cognitive alterations and imaging findings related to MCD and dementia [ 90 92 ]. Both microcirculatory and neurodegenerative changes in the retina and cornea are associated with cognitive changes and dementia, but the better marker and the mechanisms involved have not been fully elucidated [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, people may experience difficulty with "seeing" more than one thing at a time, which is referred to as "simultanagnosia", grasping the "big picture", and selecting something specific from among a cluster of items [15,115]. Changes in vision are significant to the extent that differences in the retina are being explored as an option for early detection of neurodegenerative changes associated with mild cognitive impairment and Alzheimer's disease [2,14,47,68,106]. Other visual changes may include visual hallucinations, which are more typical for dementia with Lewy bodies [97].…”
Section: Background: Sensory Changes Unique To Age-related Cognitive ...mentioning
confidence: 99%
“…Participants described visual changes they experienced due to age-related cognitive changes that interacted with their technology use, including changes in visual acuity, color perception, ability to select an object out of a busy environment, ability to see the big picture and surface dyslexia. Changes in vision have been associated with mild cognitive impairment and Alzheimer's disease in clinical research [2,14,47,68,106].…”
Section: Visualmentioning
confidence: 99%
“…Multiple lines of evidence have shown that, in addition to the episodic memory and neuropsychiatric manifestations involving the hippocampal CA1 and temporal lobe neocortex, AD is a more globalized disorder encompassing sensory impairments in olfaction, hearing and especially vision [ 1 ]. In particular, deficits in visual system function have been described in experimental AD animal models [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] and in affected patients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] consistent with the extensive neuropathology of Aβ plaques and tau neurofibrillary tangles (NFT) in their visual primary and association cortices and sensory system, including the optic nerves and retina themselves. More importantly, in both human beings and in vivo model systems, visuo-spatial complaints and retinal functional deficits are reported to manifest in concomitance [ 23 , 24 , 25 , 26 ] or, sometimes, even precede [ 27 , 28 , 29 , 30 , 31 , 32 ], the occurrence of the signs of memory/learning deterioration traditionally associated with the clinical symptomatology of AD.…”
Section: Introductionmentioning
confidence: 99%